As estelas antropomórficas de Picote - Miranda do Douro (Trás-os-Montes) - Sanches, Maria de Jesus (2011)
The purpose of this paper is the study of a group of granite made anthropomorphic proto sculptural forms, identified at the archaeological sites of Salgueiros and Puio, during an archaeological survey at Picote, Miranda do Douro (Trás-os-Montes, Portugal). The archaeological site of Salgueiros evokes an architectonically complex structure, probably a precinct type. Due to their close proximity the archaeological sites of Salgueiros and Puio may be interpreted (in the regional pre-historic context, 4º and 3º mil. AC) as being part of the same simbolic landscape, a strategically situated area that topographically dominates a narrow curve of the Douro river. It was these characteristics that drove us to analise the stelae precinct of Cabeço da Mina (Vila Flor), which also dominates an enlarged valley, the valley of Vilariça. Likewise, this landscape (the broad Vilariça valley) appears marked not just by the precinct itself, but also by two standing stelae located at the southern entrance of the same valley. In both areas Picote, Douro valley, and Vilariça valley/base level of Sabor river the formal and iconographic analisis of the stelae suggests that we may be facing communal narratives with a genealogical character, or some other that may allow multiple readings. Given the scale of the area, we belive they would embody discourses that would make each of these precincts a place of a relatively singular meaning. However, given the context of the possible social practices that may have occured there, these places/precincts would have (or would necessarily evoke) narratives relating to the identitary character of communal relations that would vigorate among the groups that habitated this region during Pre-History.